Work Performance of Employees With Depression: The Impact of Work Stressors - Lerner, Debra (2010)
PURPOSE: Depressed employees are vulnerable to adverse work outcomes. We hypothesized that work performance is impaired by depression and is worsened by exposure to psychosocial work stressors. DESIGN: Longitudinal cohort study with surveys administered at baseline, 6, 12, and 18 months. SETTING: Recruitment in primary care offices. SUBJECTS: A total of 14,268 were screened; 286 depressed, employed adults (18–62 years) and 193 controls were enrolled. MEASURES: At-work limitations (presenteeism) and absenteeism were measured with the Work Limitations Questionnaire (WLQ) and WLQ Work Absence Module, respectively. Work stressors were assessed using a modified version of the Job Content Questionnaire. ANALYSIS: Univariate and multivariate tests assessed the degree to which at-work limitations were related to depression and/or stressful work. RESULTS: Presenteeism and absenteeism were significantly worse for the depression group at each time point (p ≤ .001). In cross-sectional models, presenteeism was associated with more severe depression symptoms, poorer general physical health, psychologically demanding work, the interaction of psychologically demanding work with depression, and less job control (r(2) range = .33–.54). Absences were explained by depression symptom severity and poorer general physical health but not work stressors (r(2) = .19). Because of minimal change in the work stressors, their longitudinal effects on outcomes were mostly nonsignificant. CONCLUSION: This study found that depression symptoms are related to work absences and impaired work performance, and results partly confirmed that work stressors add to this impact. Results suggest that workers with depression may benefit from care involving medical and vocational interventions.